2015
DOI: 10.1111/pde.12641
|View full text |Cite
|
Sign up to set email alerts
|

Dermestid Dermatitis in a 2‐Year‐Old Girl: Case Report and Review of the Literature

Abstract: Dermatitis from contact with carpet, larder, and hide beetles (family Dermestidae) is a seemingly uncommon or underrecognized hypersensitivity reaction to the specialized hairs on the larvae of certain dermestid beetles. The erythematous papulovesicular dermatitis that may result from such contact can be mistakenly construed as evidence of bites of bedbugs or other arthropods or infestation with scabies mites or can be the basis for a diagnosis of delusory parasitosis. We present a case of dermestid dermatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
4
14
0
Order By: Relevance
“…In other reports, when detection method was specified, causative arthropods were researched and identified only on focally collected dust. 6,8,9,24 We observed a higher prevalence of ectoparasitoses in females (73.5%), as reported by other Authors. 25 Gender distribution is influenced by the kind of work done, typically domestic in our study, as showed by the prevalent male involvement in occupational ectoparasitoses.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In other reports, when detection method was specified, causative arthropods were researched and identified only on focally collected dust. 6,8,9,24 We observed a higher prevalence of ectoparasitoses in females (73.5%), as reported by other Authors. 25 Gender distribution is influenced by the kind of work done, typically domestic in our study, as showed by the prevalent male involvement in occupational ectoparasitoses.…”
Section: Discussionsupporting
confidence: 89%
“…Five clinical pictures were observed in our patients (Table ). Strophulus was the most frequent clinical picture both in insect (48.8%) and mite cases (45.5%), as reported by others . Urticaria‐like eruption was the second one, while scabies‐like eruption and erythematous papular and pustular lesions (4.1% and 3.1%, respectively) were rarely observed in our study (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations